2005
DOI: 10.1007/s00431-005-1732-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term serial echocardiographic examination of late anthracycline cardiotoxicity and its prevention by dexrazoxane in paediatric patients

Abstract: Dexrazoxane seems to reduce the risk of late subclinical cardiotoxicity. Dexrazoxane-treated patients revealed better exercise tolerance; however the haemodynamic response to the stress was no different in both sub-groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…Using serial measurements of troponin I in 101 children given doxorubicin, Lipshultz et al found a lower rate of increased levels (N0.01 ng/ml) when dexrazoxane was associated (21 vs 51% of treated children) (67). Another study in 75 children treated for leukemias or lymphomas showed fewer late (8 years) impairments of LVEF, occurring in 17% of those who received dexrazoxane and 41% in its absence [68].…”
Section: Antioxidantsmentioning
confidence: 95%
“…Using serial measurements of troponin I in 101 children given doxorubicin, Lipshultz et al found a lower rate of increased levels (N0.01 ng/ml) when dexrazoxane was associated (21 vs 51% of treated children) (67). Another study in 75 children treated for leukemias or lymphomas showed fewer late (8 years) impairments of LVEF, occurring in 17% of those who received dexrazoxane and 41% in its absence [68].…”
Section: Antioxidantsmentioning
confidence: 95%
“…Es ist noch nicht ganz klar, wie der Wirkungsmechanismus ist, jedoch haben mehrere Studien gezeigt, dass Dexrazoxan die Kardiotoxizität von Anthracyclinen um 70-80% verringern kann. Einziges Caveat bleibt die Unsicherheit bezüglich einer eventuellen Reduktion der Antitumoreffizienz der Anthracycline oder eine mögliche Erhöhung der Inzidenz von Sekundär-malignomen [50][51][52][53][54][55][56][57][58][59][60]. Es sind jedoch weitere Studien notwendig, um diese vorläufigen Ergebnisse zu untermauern.…”
Section: Präventionunclassified
“…Importantly, the randomized prospective trial by Lipshultz et al has clearly shown that DEX may prevent cardiotoxicity onset in children with &2.5-year follow-up after the chemotherapy (169). A nonrandomized prospective trial by Elbl et al has suggested that DEX affords a long-term cardioprotection from both clinical and subclinical cardiotoxicity in 8-year follow-up after the ANT treatment (57). In addition, a retrospective study in children with a follow-up of 2-20 years (7 years median) suggested a reduction of both clinical and subclinical signs of late-onset cardiotoxicity in children receiving DEX (58).…”
Section: Cardioprotection Against Ant Cardiotoxicity In Clinical Trialsmentioning
confidence: 99%